La Biennale di Venezia : Dreams and conflicts : the dictatorship of the viewer. - Biennale Venetië 2003; Abdel-Moity, Mostafa; Abramović, Marina; Alimpiev, Victor; Ananth, Deepak; Andjelkovic, Branislava; Aradeon, David; Arestizabal, Irma; Baldi, Pio; Basualdo, Carlos; Bernabè, Franco; Birnbaum, Daniel; et al. (Venezia : La biennale di Venezia, 2003)
Abdessemed, Adel ; Abergel, Etty ; Abramovic, Marina ; Accardi, Carla ; Acconci Studio ; Acconci, Vito ; Ackermann, Franz ; Aitken, Doug ; Alfaro, Brooke ; Ali, Laylah ; Alimpiev, Viktor ; Allen, Dave ; Almond, Darren ; Althamer, Pawel ; Althoff, Kai ; Amielli, Liliana ; Amorales, Carlos ; Andersson, Mamma ; Angelo, Marta dell' ; Antille, Emmanuelle ; Aquilizan, Alfredo Juan ; Aquilizan, Maria Isabel ; Arahmaiani ; Arcagrup ; Ariatti, Alessandra ; Art & Language ; Assaël, Micol ; Asymptote ; Atchugarry, Pablo ; Atelier Bow-Wow ; Atelier FCJZ ; Atelier van Lieshout ; Attia, Kader ; Auerbach, Frank ; Avanguardie Permanenti ; Avery, Charles ; Avvakumov, Yuri ; Azizov, Zeigam ; Back, Ann-Sofie ; Bacon, Francis ; Bajevic, Maja ; Baldessari, John ; Balka, Miroslav ; Barcelo, Miquel ; Barclay, Claire ; Barney, Matthew ; Bärtas, Magnus ; Baselitz, Georg ; Basilè, Matteo ; Basquiat, Jean-Michel ; Bayrle, Thomas ; Bazan, Alessandro ; Beagles & Ramsay ; Bello, Paola Di ; Ben Gal, Avner ; Benyahia, Samta ; Bergamasco, Matteo ; Bhimji, Zarina ; Bilge Ceylan, Nuri ; Billing, Johanna ; Birnbaum, Dara ; Blocher, Sylvie ; Blyth, David ; Bock, John ; Bonillas, Iñaki ; Bonk, Ecke ; Book, Ingrid ; Borges Libreria / World Bookstore ; Bourgeois, Louise ; Bowling, Frank ; Braein, Kristina ; Bratkov, Sergey ; Breyter, florencia ; Broks, Ervins ; Bromová, Veronika ; Brown, Glenn ; Bruce Mau Design ; De Bruyckere, Berlinde ; Bryce, Fernando ; Bulatov, Erik ; Bulloch, Angela ; Bureau d'études ; Buren, Daniel ; Burri, Alberto ; Bustamante, Jean-Marc ; Buzari, Pash ; Caillet, Aline ; Campement Urbain ; Cantor, Mircea ; Cao Fei ; Caracas Group ; Cardoso, Maria Fernanda ; Caruso, Susana ; Cassara, Paolo ; Castellani, Enrico ; Castelli, Alberto ; Castro, Jota ; Casula, Cristina ; etc.
La Biennale di Venezia 2003, Venezia, 2003-06-15 tot 2003-11-02
boek